Optimization of Bioactive Compound Extraction from Propolis by Reflux, Maceration and Ultrasound-assisted Methods and Characterization of the Extracts - Şenol Yazkan, Sevde Nur; Hendek Ertop, Müge (Ankara University Faculty of Agriculture, 2025)
The region, botanical origin, and bee species influence the raw propolis content and its bioactive properties. Additionally, the extraction methods, solvents, and various process parameters significantly affect the bioactive properties of propolis extract, which is consumed as a food supplement or pharmaceutical product. In this study, propolis with a chestnut botanical origin, obtained from the Black Sea region in Turkey, was used as the raw material. The process parameters of three basic extraction methods— maceration (M), reflux (R), and ultrasound-assisted (UA)—were optimised using response surface methodology. Antioxidant activity (AA) and total phenolic content (TPC) were used as response parameters. The optimised levels for M were 78.46% ethanol concentration and 71.05 hours for extraction time; for R, 80.64% ethanol concentration, 117.44 minutes for extraction time, and 38.38°C for temperature; and for UA, 82.49% ethanol concentration, 59.12 minutes for extraction time, and 40.53°C for temperature. The results were statistically validated using the t-test. The AA, TPC, and phenolic, volatile, and mineral contents were compared among the optimised chestnut propolis extracts. Chrysin, a flavone, and pinocembrin, a flavanone, along with ferulic and ellagic acid, among the phenolic acids, were identified as the most abundant phenolic compounds. Among the 11 elements, the highest macro elements were Na, K, and Ca, while the trace elements were Fe and Zn. The phenolic, volatile, and mineral compositions of the optimised propolis extracts exhibited heterogeneous distributions. However, fatty acids (e.g., 18:0, 18:1) were present at relatively high levels only in R; phenolic compounds were obtained in relatively high amounts via M extraction. Some minor volatiles were detected only by UA extraction. Following the characterisation of the optimised extracts, it was determined that each extraction method has its own unique advantages. The results indicate that all three methods should be optimised and used together to achieve the highest component composition and bioactivity.
Keywords: Food supplement; bee products; Response surface methodology; bioactivity; Basic Food Processes; Temel Gıda İşlemleri